Investigation of the Active Ingredients and Mechanism of Polygonum cuspidatum in Asthma Based on Network Pharmacology and Experimental Verification - Bi J; Lin YH; Sun Y; Zhang M; Chen Q; Miu X; Tang L; Liu J; Zhu L; Ni Z; Wang X (Dove Medical Press, 2021)
Junjie Bi,1,* Yuhua Lin,1,* Yipeng Sun,1,* Mengzhe Zhang,2,* Qingge Chen,1 Xiayi Miu,1 Lingling Tang,1 Jinjin Liu,1 Linyun Zhu,1 Zhenhua Ni,3 Xiongbiao Wang1 1Department of Respiratory Medicine, Putuo Hospital, Shanghai University of Traditional Chinese Medicine, Shanghai, 200062, People’s Republic of China; 2Department of Laboratory Medicine, Putuo Hospital, Shanghai University of Traditional Chinese Medicine, Shanghai, 200062, People’s Republic of China; 3Central Laboratory, Putuo Hospital, Shanghai University of Traditional Chinese Medicine, Shanghai, 200062, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhenhua Ni; Xiongbiao Wang Email zhenhuani@yeah.net; xiongbiao6@yahoo.comBackground: Polygonum cuspidatum is a Chinese medicine commonly used to treat phlegm-heat asthma. However, its anti-asthmatic active ingredients and mechanism are still unknown. The aim of this study was to predict the active ingredients and pathways of Polygonum cuspidatum and to further explore the potential molecular mechanism in asthma by using network pharmacology.Methods: The active ingredients and their targets related to Polygonum cuspidatum were seeked out with the TCM systematic pharmacology analysis platform (TCMSP), and the ingredient-target network was constructed. The GeneCards, DrugBank and OMIM databases were used to collect and screen asthma targets, and then the drug-target-disease interaction network was constructed with Cytoscape software. A target protein-protein interaction (PPI) network was constructed using the STRING database to screen key targets. Finally, GO and KEGG analyses were used to identify biological processes and signaling pathways. The anti-asthmatic effects of Polygonum cuspidatum and its active ingredients were tested in vitro for regulating airway smooth muscle (ASM) cells proliferation and MUC5AC expression, two main symptoms of asthma, by using Real-time PCR, Western blotting, CCK-8 assays and annexin V-FITC staining.Results: Twelve active ingredients in Polygonum cuspidatum and 479 related target proteins were screened in the relevant databases. Among these target proteins, 191 genes had been found to be differentially expressed in asthma. PPI network analysis and KEGG pathway enrichment analysis predicted that the Polygonum cuspidatum could regulate the AKT, MAPK and apoptosis signaling pathways. Consistently, further in vitro experiments demonstrated that Polygonum cuspidatum and resveratrol (one active ingredient of Polygonum cuspidatum) were shown to inhibit ASM cells proliferation and promoted apoptosis of ASM cells. Furthermore, Polygonum cuspidatum and resveratrol inhibited PDGF-induced AKT/mTOR activation in ASM cells. In addition, Polygonum cuspidatum decreased H2O2 induced MUC5AC overexpression in airway epithelial NCI-H292 cells.Conclusion: Polygonum cuspidatum could alleviate the symptoms of asthma including ASM cells proliferation and MUC5AC expression through the mechanisms predicted by network pharmacology, which provides a basis for further understanding of Polygonum cuspidatum in the treatment of asthma.Keywords: Polygonum cuspidatum, asthma, ASM cells, MUC5AC, network pharmacology